Research on load transfer planning model for equipment maintenance in the substation - Zhang, Kanjun; Wang, Ting; Zhou, Hubing; Li, Hengxuan; Tang, Aihong; Yang, Huiyuan; Peng, Jiao (Frontiers in Energy Research, 2023)
The maintenance, inspection, and refurbishment of substation equipment are crucial for ensuring the stability of the power grid's operation and the reliability of power supply to users. However, currently, there is a lack of methods for rapidly and effectively planning load transfer solutions during substation equipment maintenance periods. To address this, this study is founded on the principles of transmission network planning theory, and an analysis of the similarities and disparities between the planning methods for load transfer solutions during substation equipment maintenance and traditional approaches to transmission network planning is conducted. Furthermore, this paper integrates practical constraints related to maintenance engineering and power grid load flow balance constraints. With the primary optimization objectives of minimizing investment and operational costs during system maintenance while maximizing power grid reliability, a load transfer planning model for equipment maintenance in the substation has been developed. Simultaneously, in conjunction with linear programming theory, the nonlinear constraint terms of the model have been equivalently simplified to enhance the computational performance of the model. Simulation analysis is conducted on case studies constructed based on the IEE-RBTS6 and IEEE-RTS79 systems to validate the effectiveness of the proposed model in solving the optimal maintenance planning problem.